The difference of human gut microbiome in colorectal cancer with and without metastases - Sun, Leitao; Zhu, Zhenzheng; Jia, Xinru; Ying, Xiangchang; Wang, Binbin; Wang, Peipei; Zhang, Shuo; Yu, Jieru (Frontiers in Oncology, 2022)
Metastasis of colorectal cancer is deemed to be closely related to the changes in the human gut microbiome. The purpose of our study is to distinguish the differences in gut microbiota between colorectal cancer with and without metastases. Firstly, this study recruited colorectal cancer patients who met the established inclusion and exclusion criteria in the Oncology Department of Zhejiang Hospital of Traditional Chinese Medicine from February 2019 to June 2019. Fresh stool samples from healthy volunteers, non-metastatic patients, and metastatic patients were collected for 16S rRNA gene sequencing, to analyze the diversity and abundance of intestinal microorganisms in each group. The results showed that the microbial composition of the control group was more aplenty than the experimental group, while the difference also happened in the Tumor and the metastases group. At the phylum level, the abundance of Bacteroidetes significantly declined in the Tumor and the metastases group, compared with the control group. At the class level, Bacilli increased in experimental groups, while its abundance in the Tumor group was significantly higher than that in the metastases group. At the order level, the Tumor group had the highest abundance of Lactobacillales, followed by the metastases group and the control group had the lowest abundance. Overall, our study showed that the composition of the flora changed with the occurrence of metastasis in colorectal cancer. Therefore, the analysis of gut microbiota can serve as a supplement biological basis for the diagnosis and treatment of metastatic colorectal cancer which may offer the potential to develop non-invasive diagnostic tests.